Pregnancy intentions among female sex workers: recognising their rights and wants as mothers. Issue 2 (23rd July 2014) - Duff, Putu; Shoveller, Jeannie; Feng, Cindy; Ogilvie, Gina; Montaner, Julio; Shannon, Kate
Abstract : Objective: To better understand the prevalence and correlates of pregnancy intentions among female sex workers (FSWs). Design: Cross-sectional analysis using data from an open prospective cohort of street and off-street FSWs in Vancouver, Canada, in partnership with local sex work and community agencies. Methods: FSWs were recruited through outreach to street and off-street locations (e.g. massage parlours, micro-brothels) and completed interviewer-administered questionnaires and HIV/sexually transmitted infection testing. Bivariable and multivariable logistic regression was used to evaluate correlates of pregnancy intention, based on a 'yes' or 'no' response to the question "Are you planning on have any (any more) children in the future?". Results: Of the 510 women, 394 (77.3%) reported prior pregnancy, with 140 (27.5%) of the entire sample reporting positive pregnancy intentions. Regarding ethnicity, 35.3% were Caucasian and 26.3% were Asian/visible minority, with no differences in pregnancy intention by ethnicity or HIV status; 38.4% reported Canadian Aboriginal ancestry. In our final multivariable model, servicing clients in formal indoor settings, inconsistent condom use by clients, younger age, and intimate partner violence (IPV) were associated with pregnancy intention. Conclusions: FSWs may have pregnancy intention levels similar to that of women in other occupations. Policy changes are needed to improve FSWs' access to integrated HIV and reproductive health services and harm reduction services, particularly for FSWs experiencing IPV.